Black consciousness revived: the rise of black consciousness thinking in South African student politics - Sikhosana, Nompumelelo Pertunia (My University, 2017)
The history of segregation in South Africa is well documented. The shadows of the apartheid system still linger in society to date, especially in the form of racial inequality, race consciousness and racial classification. Contemporary student protests and vandalism in institutions of higher education reveal deep-seated tensions that open a can of worms concerning race and equality – elements that have long been of concern in the Black Consciousness Movement and its ideology in the early 1960s and 70s. This research report assesses how Black Consciousness tenets’ and rhetoric are re-emerging in the current national student movement, from the #RhodesMustFall to the #FeesMustFall movements. Black Consciousness ideology in South Africa, as articulated by Biko, sought the attainment of a radical egalitarian and non-racial society. Amongst some of the espoused principles of the Black Consciousness Movement that defined South African youth politics in the 1970s, is that Black Consciousness emphasised values of black solidarity, self-reliance, individual and collective responsibility, and black liberation. The year 2015 witnessed the resurgence of Black Consciousness language at the forefront of student movements, most notably the #RhodesMustFall and the #FeesMustFall campaigns. The #FeesMustFall movement and its supporters uphold that their cause is legitimate because it does not make sense for household incomes to depreciate next to escalating costs of living and rising tuition fees. It further states that the ANC fears it because its demands stand contrary to ANC-led government’s interests and have accused the ANC of attempting to capture the movement – hence the declaration that #FeesMustFall is a direct critique of the entire socio-economic and political order of the ruling ANC and exposes ANC corruption and betrayal. The movement continues, though its cause tends to be diluted and convoluted, the struggle is real but so is the legacy of Biko and the spirit of Black Consciousness.
University of the Witwatersrand Faculty of Humanities Political Studies Master’s Research Report, February 2017
Keywords: Black Consciousness Movement of South Africa; College students--Political activity; Black--Race identity--South Afric; Blacks--South Africa--Politics and government; South Africa--Race relations